Biosynthetic origin of alkylated decaline-type polyketides and induction of a new metabolite by addition of benzoate in cultured mycobionts of Pyrenula sp. (August 2018) - Takenaka, Yukiko; Tanahashi, Takao
Graphical abstract: Highlights: The biogenetic origin of pyrenulic acid C was verified by feeding experiments. The cultured mycobionts produced pyrenulic acid I by addition of benzoate to medium. The structure of pyrenulic acid I was spectroscopically determined. Abstract: The assembly pattern of acetate units and methyl groups in the biosynthesis of a polyketide, pyrenulic acid C (1 ), in cultured mycobionts of a Vietnamese Pyrenula sp. was verified by administration of sodium [1- 13 C]-acetate, sodium [1, 2- 13 C2 ]-acetate, and L-[methyl- 13 C]-methionine. The cultured mycobionts were induced to produce a new polyketide, pyrenulic acid I (2 ), by addition of sodium benzoate to malt-yeast extract medium supplemented with 5% sucrose. Its structure was determined by spectroscopic methods.